2017
DOI: 10.1161/strokeaha.116.015857
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes After Direct Thrombectomy or Combined Intravenous and Endovascular Treatment Are Not Different

Abstract: Five recent randomized controlled trials provided clear evidence that endovascular thrombectomy (EVT) improves outcomes after acute ischemic stroke caused by large vessel occlusions (LVOs), [1][2][3][4][5] and current guidelines recommend EVT in addition to intravenous thrombolysis (IVT) within 4.5 hours among patients with anterior circulation strokes and LVO. 6,7 Patients eligible for IVT should receive it without delay even if EVT is being considered, but the particular benefit of IVT is not yet well est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 12 publications
4
47
0
1
Order By: Relevance
“…In the present study, age and admission NIHSS were identified as prognostic factors on multivariate analyses but treatment allocation did not influence outcome. This is in agreement with a smaller single-center pilot study that examined the effects of bridging versus dEVT on outcome and found no such impact [18] as well as with several other retrospective studies [22,23,[33][34][35] and prospective registry data [20,21,24] that did not find differences in outcome between patients treated with bridging and those treated with dEVT. In contrast, other retrospective studies found lower mortality rates [23], lower symptomatic hemorrhage rates and higher reperfusion rates in patients treated with dEVT [36] while two meta-analyses on the subject found evidence for lowering mortality and severe disability rates with bridging [26,37].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study, age and admission NIHSS were identified as prognostic factors on multivariate analyses but treatment allocation did not influence outcome. This is in agreement with a smaller single-center pilot study that examined the effects of bridging versus dEVT on outcome and found no such impact [18] as well as with several other retrospective studies [22,23,[33][34][35] and prospective registry data [20,21,24] that did not find differences in outcome between patients treated with bridging and those treated with dEVT. In contrast, other retrospective studies found lower mortality rates [23], lower symptomatic hemorrhage rates and higher reperfusion rates in patients treated with dEVT [36] while two meta-analyses on the subject found evidence for lowering mortality and severe disability rates with bridging [26,37].…”
Section: Discussionsupporting
confidence: 90%
“…Rapid target vessel recanalization is associated with higher chances for favorable outcome in patients with large-vessel occlusion [16,17] and therefore early direct EVT (dEVT) may be advantageous in these patients by shortening the time to reperfusion [18,19]. Several recent studies looked at individual or pooled data from recent observational or randomized studies yielding conflicting results [20][21][22][23][24][25][26]. Thus, while most did not find differences in outcome between dEVT and bridging [20,22,24], some found advantages for dEVT [21,25], while still others were able to detect benefit for bridging over dEVT [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, there are conflicting results about whether preinterventional IV rtPA actually increases the risk of HTs after ET or not [8,47,48,49,50,51]. Somewhat counterintuitive, we have found that eligibility for IV rtPA bridging was associated with a decreased risk of subsequent HI.…”
Section: Discussionmentioning
confidence: 65%
“…The first important result was that the prevalence of OD, evaluated by clinical methods, was 45.06%, which is a bit lower than previously reported results, using similar methods (51‐55%). This difference could be explained by the fact that our population had less severe stroke than other studies as the more severe cases were referred to a tertiary stroke center close to our hospital; there patients could undergo thrombectomy and invasive treatments according to The Catalan Stroke Code and Reperfusion Consortium, as explained in the exclusion criteria of our patients. Another reason why our patients were less severe is because some patients in a critical state were not able to sign the Informed Consent and could not enter the study.…”
Section: Discussionmentioning
confidence: 97%